Cilka's journey - Morris, Heather (Screenwriter) (New York : St. Martin's Press, 2019)
"Cilka is just sixteen years old when she is taken to Auschwitz-Birkenau Concentration Camp in 1942, where the commandant immediately notices how beautiful she is. Forcibly separated from the other women prisoners, Cilka learns quickly that power, even unwillingly taken, equals survival. When the war is over and the camp is liberated, freedom is not granted to Cilka: She is charged as a collaborator for sleeping with the enemy and sent to a Siberian prison camp...In Siberia, Cilka faces challenges both new and horribly familiar, including the unwanted attention of the guards. But when she meets a kind female doctor, Cilka is taken under her wing and begins to tend to the ill in the camp, struggling to care for them under brutal conditions"--
"A novel" -- Cover.
Keywords: Birkenau (Concentration camp) -- Fiction; Women prisoners -- Russia -- Siberia -- Fiction; Ex-concentration camp inmates -- Fiction; Siberia (Russia) -- Fiction; Historical fiction